Influence of Motivation Factor on Consumer Engagement and Purchasing Intention for Moselo.com (The Indonesian Journal of Business Administration, 2021)
Technology as main drivers of economy and the government were also aware of the change, therefore, government has been aware of the importance of the creative economy for turning the Indonesian economy's wheels. The creative economy were divided into 17 sectors which culinary, fashion and craft as the three main sector that contribute in Indonesia GDP. Moselo were an e- commerce platform that engage in the field of craft and illustration which established from PT. Komunitas Karya Kencana in 2017. The aims of this study is to enhancing brand awareness and purchase intention for Moselo brand using motivation as a drivers. Moselo were realized that motivation of their customer were impacting the brand awareness and purchase decision. The lack of brand awareness of Moselo among the audience were the main issues of this study. There are three motivation that could influence consumer engagement that may impact brand awareness and purchase intention, the motivation is hedonic motive, utilitarian motive and social motive. The data were collected in two types, the primarily data were collected from 50 respondents as a supporting data for business issue, and the study data were collected from 210 respondents from Bandung, Jakarta, Bekasi, Central Java, East Java, Sulawesi, Kalimantan, Bali and Sumatera with the age range of respondents in 20-35 years old. The data was distribute used online questionnaire and processed using partial least square (PLS) estimation. The result for the study is the social motivation were significant for consumer engagement and the consumer engagement were also significant for brand awareness, therefore, brand awareness significant related to purchase intention. Among the six factor there are two motivation the hedonic and utilitarian factor that insignificant for the model. The overall analysis result generate business solution using point of parity (POP) and point of difference (POD) also purchasing decision process approaches. Furthermore, researcher were formulated 5 alternative solution such as developing brand ambassador, contest, video advertising, Instagram content and social media ads. The solution were related to one and another and could be implemented for Moselo to increase brand awareness and purchase intention.Keywords: E-Commerce, Motivation, Consumer Engagement, Craft